What consistent responses on future inflation by consumers can reveal - Sarah Miller; Patrick Sabourin (Bank of Canada, 2023)
Inflation expectations play a vital role in determining inflation. Central bankers need to understand their intricacies and the information they can reveal. We look at the consistency of consumers' answers to questions on inflation expectations in the Bank of Canada's Canadian Survey of Consumer Expectations. We analyze factors that may explain consistencies among individuals and overall. We also compare the inflation forecasts of consumers with consistent responses with those of professional forecasters and consumers with varying responses.
Keywords: E31; D80; D84; 330; Central bank research; Inflation and prices